2014
DOI: 10.1155/2014/656370
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation Antipsychotics and Extrapyramidal Adverse Effects

Abstract: Antipsychotic-induced extrapyramidal adverse effects are well recognized in the context of first-generation antipsychotic drugs. However, the introduction of second-generation antipsychotics, with atypical mechanism of action, especially lower dopamine receptors affinity, was met with great expectations among clinicians regarding their potentially lower propensity to cause extrapyramidal syndrome. This review gives a brief summary of the recent literature relevant to second-generation antipsychotics and extrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
186
3
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(204 citation statements)
references
References 40 publications
5
186
3
10
Order By: Relevance
“…Таким образом, антипсихотики второго поколения не вполне оправдали ожидания клиницистов относительно их безопасности, и осложнения психотропной терапии экстрапирамидного спектра остаются клинически важ-ными в эпоху их применения [24].…”
Section: журнал неврологии и психиатрии 4 2015 обзорыunclassified
“…Таким образом, антипсихотики второго поколения не вполне оправдали ожидания клиницистов относительно их безопасности, и осложнения психотропной терапии экстрапирамидного спектра остаются клинически важ-ными в эпоху их применения [24].…”
Section: журнал неврологии и психиатрии 4 2015 обзорыunclassified
“…Schizophrenic patients are treated with Second-Generation Antipsychotic Drugs (SGAs) such as risperidone, olanzapine, quetiapine and aripiprazole and, in some cases, with First-Generation Antipsychotic Drugs (FGAs) such as haloperidol [3]. Adverse effects of the FGAs and to a lesser extent of the SGAs are Extrapyramidal Symptoms (EPS), for example Parkinsonism, dystonia, dyskinesia or oculogyric crises [4]. These adverse effects are due to the blockade of D2 dopaminergic receptors in the extrapyramidal system.…”
Section: Introductionmentioning
confidence: 99%
“…These adverse effects are due to the blockade of D2 dopaminergic receptors in the extrapyramidal system. It has been reported that recent developed antipsychotic drugs exert a mechanism of action different from the blockade of the D2 receptor and cause less often EPS [4].…”
Section: Introductionmentioning
confidence: 99%
“…Clozapine improves positive and negative symptoms, while inducing minimal extrapyramidal side effects (Divac et al, 2014). Clozapine and its predominant active metabolite, N-desmethylclozapine (NDMC), have complex pharmacological profiles, and interact with a wide range of neurotransmitter receptors including dopamine, serotonin, norepinephrine, histamine and acetylcholine receptors (Correll, 2010;Lameh et al, 2007;Mendoza and Lindenmayer, 2009;Weiner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%